Ccomplexos de PdII, PtII e AuIII com tiossemicarbazonas derivadas da diacetilmonooxima: síntese, caracterização, atividade antitrypanozoma cruzi e citotoxidade - GONÇALVES, Ana Cristina Resende (2016)
Chagas disease affects approximately 8 million people worldwide. Unfortunately, the treatment of this disease is limited to two drugs, the nitroheterocyclics compounds benznidazole and nifurtimox, which lead to severe side effects, besides being inefficient in the chronic phase of the disease. In this sense, compounds belonging to the class of the thiosemicabazones have attracted the attention of many researchers due to the known trypanocidal activity of such compounds. On the other hand, oxime containing compounds are commonly used in the medicine as chelating agents in instant kits for preparation of 99mTc radiopharmaceuticals. Therefore, the combination of both classes seems to be suitable for the acquirement of chelating agents which could be used in the complexation of transition metals and then give origin to new drugs with potential to affect multiple targets of the Trypanosoma cruzi, parasite responsible for Chagas disease. Based on this fact, the main objective of this work was to explore the synthesis and characterization of new PtII, PdII and AuIII complexes containing a thiosemicarbazone ligand derived from diacetylmonooxime (H2L) and also to change the ligands at the fourth coordination site. In total, ten complexes were synthesized starting from the diacetylmonooxime-ethyl-thiosemicarbazone (H2L1) ligand, which are divided in the text into three classes of compounds with inherent characteristics: (i) Halogen containing complexes: [MX(HL1)] (M = PtII or PdII, X = Cl– or I–) and [MX(L1)] (M = AuIII, X = Cl); (ii) Triphenylphosphane containing complexes: [M(L1)(PPh3)] (M = PtII, PdII); (iii) PtII polinuclear complexes. The yields of the reactions to prepare the complexes containing the chlorido, iodido, triphenylphosphano ligands and the polynuclear complexes were around 60%, 80%, 50% and 50%, respectively. The structural elucidation and properties of the compounds were determined with basis on the following techniques: elemental analysis (CHNS), melting point determination, conductometry, UV-Vis and FTIR spectroscopies, NMR (1H and 31P), mass spectrometry and X-ray diffraction on single crystal. After the complete characterization, the in vitro trypanocidal activity and the cytotoxicity of H2L1 and of the mononuclear compounds were evaluated. The trypanocidal activity of the free ligand (H2L1) and its derivatives was assessed against CL Brener strains of T. cruzi, which showed cytotoxic concentration (CC50try) in the range of 2.37 µM to 104.8 µM. Moreover, in order to calculate the selectivity index (SI), the cytotoxicity of the compounds was also determinedagainst the normal cells of the LLC-MK2 cell line, showing cytotoxic concentration (CC50) with values ranging from 1.9 µM to 500 μM. The results revealed that the complexation of the thiosemicarbazone ligand H2L1 to the metal centers PtII, PdII and AuIII increases the in vitro trypanocidal activity and that the cytotoxicity against normal cells is dependent on the metal center as well as on the ancillary ligands. Within the studied series, the AuIII complex showed the greater potential, with a SI higher than 87.9, consequently, being indicated for further biological studies and as a strong candidate to be used as a Chagas’ disease treatment agent.